Price Elasticities and Social Health Insurance Choice in Germany: A Dynamic Panel Data Approach - Stefan Greß; Marcus Tamm; Harald Tauchmann; Jürgen Wasem (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
In 1996 free choice of health insurers has been introduced in the German social health insurance scheme. Competition between insurers was supposed to increase efficiency. A crucial precondition for effective competition among health insurers is that consumers search for lower-priced health insurers.We test this hypothesis by estimating the price elasticities of insurers? market shares. We use unique panel data and specify a dynamic panel model to explain changes in market shares. Estimation results suggest that short-run price elasticities are smaller than previously found by other studies. In the long-run, however, estimation results suggest substantial price effects.
Keywords: C33; I18; 330; Competition; generalized method of moments; health insurance